(untitled) (Ameghiniana, 2014)
Ten species belonging to seven genera of the Ostreoidea are recognized, as a result of a taxonomic revision of the oysters from the Cretaceous-Paleogene in the Neuquen Basin, westcentral Argentina. The material was collected from the Maastrichtian Jagüel Formation and the Maastrichtian-Danian Roca Formation. Four taxa, Amphidonte mendozana (Ihering), Ambigostrea c1arae (Ihering), Gyrostrea lingua (Carnacho), and Pycnodonte (Phygraea) vesicularis (Lamarck) are Maastrichtian in age. Pycnodonte (Phygraea) burckhardti (Bohm) and Gryphaeostrea callophyia (Ihering) ha ve been recorded in the lower pan of the Roca Formation (early Danian). Ostrea neuquena Ihering occurs in Danian limestones of the middle part of the Roca Formation. Pycnodonte (Phygraea) sarmientoi n. sp. and Cubitostrea ameghinoi (Ihering) are represented in the late Danian. OSI/’ea wilckensi Ihering is recorded from beds ranging from Maastrichtian to Danian in age. Comparison of the fauna with Cretaceous and PaIeogene faunas of southern Patagonia and Antarctica indicates that the Neuquen fauna was infIuenced by dispersal from lower latitude Tethyan sources, in marked contrast to the high latitude Pacific affinities of the faunas of southern Patagonia.